2016
DOI: 10.4103/0253-7613.194853
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Celastrus paniculatus on chronic stress-induced cognitive impairment

Abstract: Objective:Several studies report that chronic stress results in impaired spatial learning and working memory and enhanced anxiety-like behavior. However, not many studies have looked into the possible ways of reversing stress-induced deficits. Celastrus paniculatus (CP), a traditional ayurvedic herbal medicine, was used to treat cognitive deficits in mentally retarded children. CP oil has been reported to have neuroprotective and antioxidant activities. However, the effects of CP oil on chronic stress-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…In the current study, chronic restraint stress enhanced anxiety‐like behavior in the EPM. Previous studies have confirmed enhanced anxiety in different chronic stress models (Anuradha et al, ; Chiba et al, ; Bhagya et al, ). Stress + EE rats showed increased time and entries in the open arms, thus indicating an anxiolytic effect of EE in chronically stressed rats.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In the current study, chronic restraint stress enhanced anxiety‐like behavior in the EPM. Previous studies have confirmed enhanced anxiety in different chronic stress models (Anuradha et al, ; Chiba et al, ; Bhagya et al, ). Stress + EE rats showed increased time and entries in the open arms, thus indicating an anxiolytic effect of EE in chronically stressed rats.…”
Section: Discussionmentioning
confidence: 76%
“…We observed impaired spatial working memory in rats exposed to chronic restraint stress. Previous studies from our lab showed that chronic restraint stress impairs spatial learning and memory in T‐maze and partially baited radial arm maze tasks (Sunanda et al, ; Srikumar et al, ; Ramkumar et al, ; Veena et al, ; Bhagya et al, ). We also observed decreased hippocampal LTP in response to restraint stress, which is in accordance with previous studies (Shors et al, ; Cui et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations